New world Hasidim : ethnographic studies of Hasidic Jews in America - Belcove-Shalin, Janet S., 1954- (State University of New York Press, 1995)
Annotation Hasidim has long been the subject of historical, philosophical, and literary accounts, but it is only in recent years that it has begun to attract the close attention of social scientists.
Keywords: Hasidism -- United States.; Hasidism -- United States -- Social conditions.; Jews -- United States -- Politics and government.; Habad -- United States.; United States -- Ethnic relations.; Hassidisme -- États-Unis.; Hassidisme -- États-Unis -- Conditions sociales.; Habad -- États-Unis.; États-Unis -- Relations interethniques.; SOCIAL SCIENCE -- Discrimination & Race Relations.; Ethnic relations; Habad; Hasidim -- Social conditions; Hasidism; Jews -- Politics and government; United States